Clinical‐scale production of cGMP compliant CD3/CD19 cell‐depleted NK cells in the evolution of NK cell immunotherapy at a single institution. Issue 6 (12th March 2018) - Williams, Shelly M.; Sumstad, Darin; Kadidlo, Diane; Curtsinger, Julie; Luo, Xianghua; Miller, Jeffrey S.; McKenna, David H.
Abstract : BACKGROUND: Allogeneic natural killer (NK) cell adoptive immunotherapy is a growing therapeutic option for patients. Clinical‐scale production of NK cells using immunomagnetic selection complies with current good manufacturing practices (cGMPs) and allows for closed‐system, automated purification. We report our experience with CD3/CD19 cell‐depleted (CD3/CD19dep ) NK cell production and compare to previous methods of CD3 cell depletion and CD3 cell depletion/CD56 cell enrichment. STUDY DESIGN AND METHODS: Nonmobilized mononuclear cells collected by apheresis were incubated with anti‐CD3/anti‐CD19 microbeads and depleted in an automated cell selection system (CliniMACS, Miltenyi). The NK cell–enriched products were incubated overnight in interleukin (IL)‐2 or IL‐15, washed, and resuspended prior to lot release testing and infusion. RESULTS: Since 2010, 94 freshly infusible CD3/CD19dep NK cell products were manufactured in support of eight clinical trials. Sixty‐six products were incubated in IL‐2 and 28 products in IL‐15. Processing resulted in a mean NK cell recovery of 74% and viability of 95.8%; NK cells, T cells, B cells, and monocytes accounted for 47%, 0.2%, 0.08%, and 49% of the final products, respectively. Seven products required dose adjustments to meet lot release. The specification for purity changed throughout the evolution of manufacturing. IL‐2 or IL‐15 activation enhanced in vitro cytotoxicity compared to preactivated cells. There was no difference in final product composition or cytotoxicity between cytokine cohorts. CONCLUSION: Clinical‐scale/cGMP production of NK cells using CD3/CD19 cell‐depletion effectively minimized T‐cell and B‐cell contamination in a single manipulation without compromise to NK‐cell recovery. Cytokine activation increased in vitro cytotoxicity compared to column‐depleted, preactivated NK cells.